Drug‐drug interactions between triazole antifungal agents used to treat invasive aspergillosis and immunosuppressants metabolized by cytochrome P450 3A4. Issue 5 (28th September 2017) - Groll, Andreas H.; Townsend, Robert; Desai, Amit; Azie, Nkechi; Jones, Mark; Engelhardt, Marc; Schmitt‐Hoffman, Anne‐Hortense; Brüggemann, Roger J. M.
Abstract: Patients undergoing treatment with immunosuppressant drugs following solid organ or hematopoietic stem cell transplantation are at particular risk for development of serious infections such as invasive aspergillosis. Four triazole antifungal drugs, voriconazole, posaconazole, itraconazole, and isavuconazole, are approved to treat invasive aspergillosis either as first‐ or second‐line therapy. All of these agents are inhibitors of cytochrome P450 3A4, which plays a key role in metabolizing immunosuppressant drugs such as cyclosporine, tacrolimus, and sirolimus. Thus, co‐administration of a triazole antifungal drug with these immunosuppressant drugs can potentially increase plasma concentrations of the immunosuppressant drugs, thereby resulting in toxicity, or upon discontinuation, inadvertently decrease the respective concentrations with increased risk of rejection or graft‐versus‐host disease. In this article, we review the evidence for the extent of inhibition of cytochrome P450 3A4 by each of these triazole antifungal drugs and assess their effects on cyclosporine, tacrolimus, and sirolimus. We also consider other factors affecting interactions of these two classes of drugs. Finally, we examine recommendations and strategies to evaluate and address those potential drug‐drug interactions in these patients.